INKUIRI-REFLEKTIF: PARADIGMA PENDIDIKAN IPS YANG TERABAIKAN - Farisi, Mohammad Imam (Universitas Negeri Semarang, 2016)
This paper describes the result of philosophical inquiry about the existence and development of inquiry-reflective paradigm of the Social Studies in the scholar community thoughts, and the curriculum development within the schools' level. Analysis focused on the social studies competences to be achieved (objectives); approaches need to be done (methods); learning contents need to be given (content). The analysis shows that the development paradigm-reflective inquiry at the social studies community is still the academic discourse, and not been yet a shared commitment. In fact, there are strong indications of the paradigm in Indonesia have 'stagnant’. The Social Studies curriculum also not consistently provides space for the development of inquiry-reflective thinking skills in a whole.